Dynamic Stress Analysis of Skin (Bovine) and Synthetic Skin (Silicone) under Low Impact Loading : a Review and Framework - Adam Mohd Adnan, Zurri; Mahmud, Jamaluddin; Azman Yahaya, Mohd (International Journal of Engineering and Technology, 2018)
Skin performs multiple important functions for our body and that might be the main reason for it complex structure and unique mechanical behaviour. There have been a lot of studies about skin mechanical behaviour but skin deformation behaviour and its dynamic stress under low impact loading is still not well understood. This paper aims to review past research related to skin investigation, which ultimately leads to proposing a research framework in determining the dynamic stress of skin and synthetic skin under low impact loading. In the first stage, the literatures related to skin substitutes and skin hyperelastic properties were reviewed, summarised and reported. The past research related to numerical analysis using hyperelastic constitutive models such as Neo-Hookean, Mooney-Rivlin and Ogden model to quantify skin mechanical behaviour were discussed. Next, the literatures related to determining dynamic stress as well as the specimen specification were reviewed and reported. Finally, based on these reviews, a research framework to determine the dynamic stress of skin and synthetic skin under low impact loading is proposed. The information provided in this paper could contribute significant fundamental knowledge about skin behaviour and the preparation to perform experiments in understanding the dynamic stress of skin under low impact loading.Â Â